2016
DOI: 10.1017/s2045796016000561
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia among patients with systemic lupus erythematosus: population-based cross-sectional study

Abstract: We found a positive association between SLE and schizophrenia across patients of different age, gender and SES. This association can contribute to understanding the pathophysiology of the two disorders and may also have clinical implications for earlier as well as better diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…The study has an observational design and not an interventional one, which is an inherent limitation to any cross‐sectional study of this type. Previous experience with the CHS population‐based study has indicated that the data are of high quality and that the associations that were detected were identical to those that were observed when smaller groups of patients with definite diagnoses were used . Our study revealed statistically significant difference towards medium (but not high) SES among RA patients as compared with controls, but the difference was small and without an overt clinical impact.…”
Section: Discussionsupporting
confidence: 79%
“…The study has an observational design and not an interventional one, which is an inherent limitation to any cross‐sectional study of this type. Previous experience with the CHS population‐based study has indicated that the data are of high quality and that the associations that were detected were identical to those that were observed when smaller groups of patients with definite diagnoses were used . Our study revealed statistically significant difference towards medium (but not high) SES among RA patients as compared with controls, but the difference was small and without an overt clinical impact.…”
Section: Discussionsupporting
confidence: 79%
“…These diagnoses were extracted from the Clalit Health Services chronic diseases registry, in the same fashion as SLE diagnosis, based on data from hospital and primary care physicians’ reports. The validity of diagnoses in the registry was previously found to be high .…”
Section: Methodsmentioning
confidence: 98%
“…1). The validity of the diagnoses in the registry, which are based on hospital and primary care physicians and specialists’ reports, was found to be high in previous studies [21, 22]. Our group has recently published several papers investigating comorbidities among RA patients based on the CHS database using similar investigational methodology [13, 23-25].…”
Section: Methodsmentioning
confidence: 99%